2020
DOI: 10.2106/jbjs.18.01305
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Myocardial Injury and Cardiovascular Outcomes of Orthopaedic Surgery

Abstract: Background: Myocardial injury after noncardiac surgery (MINS) is common and of prognostic importance. Little is known about MINS in orthopaedic surgery. The diagnostic criterion for MINS was a level of ≥0.03 ng/mL on a non-high-sensitivity troponin T (TnT) assay due to myocardial ischemia. Methods: We undertook an international, prospective study of 15,103 patients ≥45 years of age who had inpatient noncardiac surgery; 3,092 underwent orthopaedic surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Postoperative elevation of cardiac troponins often accompanies hip fracture surgery and is associated with cardiac complications in the early postoperative period, as well as with higher 30-day and annual mortality rates in patients older than 65 years. The risks of MINS are incomparably higher in orthopaedic operations, in particular, in osteosynthesis of the proximal femur, compared with other non-cardiac surgeries [8]. Therefore, ensuring adequate analgesia, prevention of cardiac, thromboembolic, infectious, pulmonary complications is the main task of the operating team.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Postoperative elevation of cardiac troponins often accompanies hip fracture surgery and is associated with cardiac complications in the early postoperative period, as well as with higher 30-day and annual mortality rates in patients older than 65 years. The risks of MINS are incomparably higher in orthopaedic operations, in particular, in osteosynthesis of the proximal femur, compared with other non-cardiac surgeries [8]. Therefore, ensuring adequate analgesia, prevention of cardiac, thromboembolic, infectious, pulmonary complications is the main task of the operating team.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…In the largest prospective studies, myocardial injury has been reported in 7.5 % to 16 % of the orthopedic procedures. 3 , 7 , 8 , 13 , 22 , 23 In patients evaluated by non hs-TnT (from the VISION study, which considered only the postoperative peak of troponin), myocardial injury occurred in 40 % of patients after amputation, 14 % after major hip or pelvic surgery, and 5 % after TKA. 13 The authors discussed that although the risk of myocardial injury varied across subcategories of orthopedic surgery, one in 20 patients had perioperative troponin elevations even in lowest-risk surgery (TKA), which was reported as quite relevant for predicting risk.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 7 , 8 , 13 , 22 , 23 In patients evaluated by non hs-TnT (from the VISION study, which considered only the postoperative peak of troponin), myocardial injury occurred in 40 % of patients after amputation, 14 % after major hip or pelvic surgery, and 5 % after TKA. 13 The authors discussed that although the risk of myocardial injury varied across subcategories of orthopedic surgery, one in 20 patients had perioperative troponin elevations even in lowest-risk surgery (TKA), which was reported as quite relevant for predicting risk. It is important to highlight that in the VISION study[7,13] myocardial injury reported as Myocardial Injury after Noncardiac Surgery (MINS) is a more restrictive term than PMI and refers to ischemic causes (in which mismatch is much more common than thrombosis) and does not include other possible causes of troponin elevation, such as pulmonary embolism or acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one recent study, 40% of patients undergoing surgery for hip fracture met criteria for MINS, with an in-hospital mortality of 11% in those with MINS versus 2.8% in those without. 45 There are no proven methods of prevention or management. The AHA has recommended routine troponin monitoring in patients at high risk of MINS, which includes many geriatric hip fracture patients.…”
Section: Fragility Fracture Managementmentioning
confidence: 99%